The politics, capital and labour of railway-building in the Cape Colony, 1870-1885 - Purkis, A (1979)
﻿ This study examines the ambitions and requirements of British financial, manufacturing and other business interests, of different territorial and economic sectors of the colonial settlement in the Cape, and of the men who laboured on the railway works, and analyzes the changing economic and political relationships between them, as manifested in the agitations and arguments leading to the decision to build railways when and where they were built and in the process of railway-building itself between 1870 and 1885. It is argued that this first, major export of British capital to South Africa after 1870, mostly for railway building (a) formed part of a wider shift in the direction of British capital investment towards parts of the Empire other than India; (b) had important implications for the constitutional development of the Cape and its political relationship with Great Britain; (c) enabled those colonial interests exercising power in the political system to determine the use made of British investments in Cape government securities, against the wishes of other colonists; (d) conditioned the relationships between British and Afrikaner colonists in the Cape; and (e) implied a new dimension to the demand for wage labour there. These developments and their implications are studied here in their inter-relation. The conclusions of the study are finally related to recent writing about the way in which Imperial economic and political interests were promoted through the collaboration of white colonial settlers.